The institutionalization of accounting: the impact of national standards on the development of economies - Semenyshena, Nataliia (2020)
The purpose of the study is to establish the essence and identification of the components of institutional accounting theory and substantiate the role and impact of these components on the national economy through the example of standardization. The author's general scheme of the institutional paradigm of institutional accounting and the approach to the development of his theory was built in the study based on a theoretical, empirical generalization, taking into account positive foreign experience, national scientific views and traditions. The examples of changes in GDP after the introduction of accounting standards (which are a structural component of institutional accounting theory) in the 6 largest countries of the world are given as an argument for the positive impact of institutional pragmatics on the national economy using the graphical method. It is proved that the dynamics that can be used to identify the impact of accounting standardization on a country's economy may be the dynamics of its GDP. The expediency of taking into account the institutional environment of Ukraine in the issues of formalization of the Institute of Accounting, as well as its political, environmental and social situation is substantiated. The conducted research confirms the influence of national peculiarities on the results of activation of institutional accounting principles and the presence of individual characteristics of values taken as arguments of indicators. It is substantiated that it is important to find effective indicators to illustrate the impact of each institutional component of accounting on the national economy.